1998
DOI: 10.1093/bja/81.6.854
|View full text |Cite
|
Sign up to set email alerts
|

Propofol infusion for induction and maintenance of anaesthesia in patients with end-stage renal disease

Abstract: We have investigated the pharmacokinetics and pharmacodynamics of propofol in 11 patients with end-stage renal disease (ESRD) compared with nine healthy patients during and after a manually controlled three-stage infusion of propofol 21, 12 and 6 mg kg-1 h-1 lasting a minimum of 2 h. Mean total body clearance was not reduced significantly in the ESRD group (30.66 (SD 8.47) ml kg-1 min-1) compared with the control group (33.75 (7.8) ml kg-1 min-1). ESRD patients exhibited a greater, but not statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…[1415] The anesthetic end-points such as patient immobility, hemodynamic stability, and maintenance of cerebral perfusion pressure, were met with. [16] As the patient was not presented with SAH or mass effect, a reduced intracranial compliance was ruled out, and normocapnia was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…[1415] The anesthetic end-points such as patient immobility, hemodynamic stability, and maintenance of cerebral perfusion pressure, were met with. [16] As the patient was not presented with SAH or mass effect, a reduced intracranial compliance was ruled out, and normocapnia was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 It has been reported that the pharmacokinetics of bolus or infusion doses are not affected markedly and can be used safely in ESRD patients. 19,20 DEX is a highly selective ␣2 adrenoceptor agonist drug with sedative, sympatholytic, and analgesic actions. It is metabolized into its inactive metabolites in liver and its elimination is unaffected by renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the PCS parameters (PCS dose of 0.2 mg·kg Ϫ1 of propofol with a delay interval of 3 min; basal infusion of 2 mg·kg·h Ϫ1 following 0.4 mg·kg Ϫ1 bolus injection) was selected based on our experience with this technique, and based on evidence [6] for the normal pharmacokinetics and pharmacodynamics of propofol even in endstage renal failure. Although these dosages were not associated with any clinically serious complications, a deeper sedation than we anticipated was observed in two of the eight patients after the start of PCS.…”
Section: Discussionmentioning
confidence: 99%